Immune-related toxic epidermal necrolysis affecting trachea mucosal epithelium: a case report and literature review - Zhang, Mingbo; Fu, Yang; Song, Yuxiao; Gao, Xia; Wang, Jun; Zhang, Bicheng (Frontiers in Pharmacology, 2024)
Background: monoclonal antibodies against pProgrammed cell death protein-1 (PD-1)/programmed death-ligand-1 (PD-L1) monoclonal antibodies have emerged as criticalcrucial tools in cancer treatmenttherapy. However, concerns regarding their potential cutaneous and mucosal toxicity, along with severe complications, have drawn clinical attention. Further research is warranted to explore investigate the adverse reactions and treatment strategies associated with PD-1 monoclonal antibodies.We present a detailed case report of a laryngeal cancer patient with laryngeal cancer who developed toxic epidermal necrolysis (TEN) following after treatment with PD-1 monoclonal antibody. By integrating clinical manifestations, pathological examinations, and literature reviews, we analyzed the etiology, diagnosis, and treatment approaches by integrating clinical manifestations, pathological examinations, and literature research.Results: After PD-1 monoclonal antibody therapy, Tthe patient exhibited systemic rash, bullae, and epidermal detachment after PD-1 monoclonal antibody therapy, which subsequently involved the tracheal and bronchial mucosa, leading toresulting in dyspnea. The patient recovered Following after treatments with steroids, macrolides, immunoglobulins, and etanercept, along with repeated removal of scabs under via bronchoscopy., the patient recovered. Literature reviewing suggests a potential association between PD-1 monoclonal antibodies and the pathogenesis of Steven Johnson's Syndrome(SJS) and /Toxic epidermal necrolysis(TEN), possibly related due to immune dysregulation. Treatment includes consists of immediate discontinuation of suspected suspicious drugs, essential supportive therapy, and systemic corticosteroid administration, with the addition of immunosuppressants and/or immunoglobulins when necessaryas needed. The mucocutaneous toxicity induced by PD-1 monoclonal antibodies is not limited to the surface of the skin but may also affect deeperin deep mucosal layers, potentially leading to lifethreatening complications. Therefore, when using PD-1 monoclonal antibodies, clinicians should closely monitor adverse events and promptly implement effectiveapply appropriate treatments as soon as possible to prevent severe complications when using PD-1 monoclonal antibodies.